2020
DOI: 10.31083/j.jin.2020.02.125
|View full text |Cite
|
Sign up to set email alerts
|

Anterior communicating artery aneurysm rupture and functional outcome in short-term: clipping versus coiling

Abstract: Our research aims to assess the change in the grade of responsiveness using the Hunt and Hess score as well as the modified ranking scale in patients suffering from anterior communicating artery rupture. We retrospectively analyzed data from 11-patients who suffered from an anterior communicating artery aneurysm rupture that caused a subarachnoid hemorrhage. Severity was assessed using the Hunt and Hess scale grade and modified ranking scale. Anterior communicating artery rupture caused a subarachnoid hemorrha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In previous comparative studies involving ruptured AComA aneurysms, procedural complications were not sufficiently characterized ( 4 , 5 , 13 , 14 , 17 , 28 ). In the post-BRAT study, Moon et al ( 3 ) reported only EVT-related complications, with major complications accounting for 3.2% and minor complications accounting for 7.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In previous comparative studies involving ruptured AComA aneurysms, procedural complications were not sufficiently characterized ( 4 , 5 , 13 , 14 , 17 , 28 ). In the post-BRAT study, Moon et al ( 3 ) reported only EVT-related complications, with major complications accounting for 3.2% and minor complications accounting for 7.5%.…”
Section: Discussionmentioning
confidence: 99%